Analisis Perbandingan Performa Algoritma Sequential Search, Binary Search, dan SQL Search pada Aplikasi Kamus Digital Bahasa Indonesia - Naufal Fadhilah; Isad Firdaus; Rakan Raihan Rasyiq (LPPM & Fakultas Teknologi Informasi UNSAP, 2025)
Scientific language is often difficult for the general public to understand, while the process of searching for meanings in conventional dictionaries is time-consuming. This issue triggers the need for digital dictionary applications equipped with fast and efficient search algorithms. This study aims to conduct a comparative performance analysis between Sequential Search, Binary Search, and SQL Search methods in an Indonesian digital dictionary application. The research method used is performance analysis by measuring two main parameters: search time speed and memory usage. Testing was conducted with word search scenarios at the beginning, middle, and end positions of the data. The results show that the Binary Search algorithm is the fastest method with an average time of 0.0405 seconds, followed by SQL Search, while Sequential Search is the slowest with an average time of 17.3785 seconds. In terms of resource efficiency, Sequential Search has the lowest memory usage due to its structural simplicity, but Binary Search remains superior in efficiency for processing large data. The conclusion of this study is that Binary Search is most effectively applied to applications with large sorted datasets, while SQL Search provides better flexibility because its data management is handled directly by the database system.Bibar